Reducing Simulated Channel Interaction Reveals Differences in Phoneme Identification Between Children and Adults With Normal Hearing. Issue 2 (March 2019) - Jahn, Kelly N.; DiNino, Mishaela; Arenberg, Julie G.
Abstract : Objectives: Channel interaction, the stimulation of overlapping populations of auditory neurons by distinct cochlear implant (CI) channels, likely limits the speech perception performance of CI users. This study examined the role of vocoder-simulated channel interaction in the ability of children with normal hearing (cNH) and adults with normal hearing (aNH) to recognize spectrally degraded speech. The primary aim was to determine the interaction between number of processing channels and degree of simulated channel interaction on phoneme identification performance as a function of age for cNH and to relate those findings to aNH and to CI users. Design: Medial vowel and consonant identification of cNH (age 8–17 years) and young aNH were assessed under six (for children) or nine (for adults) different conditions of spectral degradation. Stimuli were processed using a noise-band vocoder with 8, 12, and 15 channels and synthesis filter slopes of 15 (aNH only), 30, and 60 dB/octave (all NH subjects). Steeper filter slopes (larger numbers) simulated less electrical current spread and, therefore, less channel interaction. Spectrally degraded performance of the NH listeners was also compared with the unprocessed phoneme identification of school-aged children and adults with CIs. Results: Spectrally degraded phoneme identification improved as a function of age for cNH. For vowel recognition, cNH exhibited an interaction between the number of processing channels and vocoder filter slope, whereas aNH did not. Specifically, for cNH, increasing the number of processing channels only improved vowel identification in the steepest filter slope condition. Additionally, cNH were more sensitive to changes in filter slope. As the filter slopes increased, cNH continued to receive vowel identification benefit beyond where aNH performance plateaued or reached ceiling. For all NH participants, consonant identification improved with increasing filter slopes but was unaffected by the number of processing channels. Although cNH made more phoneme identification errors overall, their phoneme error patterns were similar to aNH. Furthermore, consonant identification of adults with CI was comparable to aNH listening to simulations with shallow filter slopes (15 dB/octave). Vowel identification of earlier-implanted pediatric ears was better than that of later-implanted ears and more comparable to cNH listening in conditions with steep filter slopes (60 dB/octave). Conclusions: Recognition of spectrally degraded phonemes improved when simulated channel interaction was reduced, particularly for children. cNH showed an interaction between number of processing channels and filter slope for vowel identification. The differences observed between cNH and aNH suggest that identification of spectrally degraded phonemes continues to improve through adolescence and that children may benefit from reduced channel interaction beyond where adult performance has plateaued. Comparison to CI users suggests that early implantation may facilitate development of better phoneme discrimination.